Iraq in the US foreign policy in the early 1990s - Filipp A. Kirichko (RUDN Journal of World History)
The relevance of the topic is due to the lingering high role of the US in the Middle East and its direct intervention in the region. As in the 1980s and the 1990s, nowadays Washington continues to directly influence the Middle East and be militarily present in it. A relevant example of this is the US comprehensive support of Israel`s war against the Gaza Strip and Lebanon and the permanent deployment of American troops in Iraq. The novelty of the research lies in the introduction of previously unused sources in Arabic into scientific circulation and in the fact that the US policy in the Middle East is being analyzed from the perspective of the serious geopolitical changes currently happening in the region. The aim of the study is to analyze the US policy towards Iraq and its characteristics on the eve of the 1990-1991 Gulf War, during and straightly after it. In the study the following methods were used: generalization, system analysis, analogy, deduction, induction, historical and comparative method. The US Middle East policy in the second half of the 20th century stood on three pillars: energy resources, supporting Israel and curbing USSR`s influence in the region. After Iraq had occupied Kuwait, the White House`s initial “playing” with president Saddam Hussein turned into a hard line aimed at weakening his regime. According to the author, Washington insisted on a military solution to the Iraqi-Kuwaiti crisis and promoted anti-Iraqi agenda, realizing that UN sanctions do not undermine the stability of Hussein`s regime. After the end of the Gulf War the US decided not to continue the military campaign against Hussein`s regime with the aim that Iraq would remain a regional counterweight to the growing Iranian influence. The Gulf War became a rehearsal for George W. Bush`s full-scale Iraqi campaign in 2003.